2006
DOI: 10.1016/j.cyto.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen and interleukin 2, 10 and 12p40 cytokine responses to measles: Is there evidence of the HLA effect?

Abstract: HLA class I and class II associations were examined in relation to measles virus-specific cytokine responses in 339 healthy children who had received two doses of live attenuated measles vaccine. Multivariate linear regression modeling analysis revealed suggestions of associations between the expression of DPA1*0201 (p=0.03) and DPA1*0202 (p=0.09) alleles and interleukin-2 (IL-2) cytokine production (global p-value 0.06). Importantly, cytokine production and DQB1 allele associations (global p-value 0.04) revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
13
0
2
Order By: Relevance
“…We have also demonstrated that HLA genes significantly influence CMI responses following MMR vaccination, but do not explain all of the variance in immune responses seen within the population (Ovsyannikova et al, 2005b(Ovsyannikova et al, , 2005c(Ovsyannikova et al, , 2006a(Ovsyannikova et al, , 2007d. For example, we have estimated that the HLA genes explain approximately 9% of the variance observed in rubella antibody levels.…”
Section: The Case Of Immune Response Heterogeneity To Vaccinesmentioning
confidence: 81%
See 1 more Smart Citation
“…We have also demonstrated that HLA genes significantly influence CMI responses following MMR vaccination, but do not explain all of the variance in immune responses seen within the population (Ovsyannikova et al, 2005b(Ovsyannikova et al, , 2005c(Ovsyannikova et al, , 2006a(Ovsyannikova et al, , 2007d. For example, we have estimated that the HLA genes explain approximately 9% of the variance observed in rubella antibody levels.…”
Section: The Case Of Immune Response Heterogeneity To Vaccinesmentioning
confidence: 81%
“…Among immune response genes, human leukocyte antigen (HLA) genes are critical genes in host immunity and vaccine immune responses. Several findings in regard to measles, mumps, rubella, influenza, and vaccinia vaccine antigens and HLA genetics were previously reported, demonstrating that HLA genes are important determinants of variability in vaccine response (Ovsyannikova et al, 2004a(Ovsyannikova et al, , 2004b(Ovsyannikova et al, , 2005a(Ovsyannikova et al, , 2006aPoland et al, 2001Poland et al, , 2008a. Our research indicates that specific HLA class I and class II gene polymorphisms, including haplotypes and supertypes, are associated with variations in MMR vaccine-induced antibody levels, demonstrating that individual genetic variation or immunogenetic profiling is important in explaining variations in protective antibody levels following vaccination (Ovsyannikova et al, 2004a(Ovsyannikova et al, , 2004b(Ovsyannikova et al, , 2005a(Ovsyannikova et al, , 2006b.…”
Section: The Case Of Immune Response Heterogeneity To Vaccinesmentioning
confidence: 99%
“…We leveraged work we previously accomplished by including subjects who had participated in our prior measles vaccine study [8;1113]. Details of recruitment of this study cohort (n=346, 12–18 years of age) are described in our previous HLA association publications [8;9;13;15].…”
Section: Methodsmentioning
confidence: 99%
“…36 In addition, HLA class II alleles can influence CD4 ϩ T-cell polarization to either the Th1 or Th2 subtype with subsequent alterations in cytokine responses. [37][38] NSHL tumors produce large amounts of Th2 and inflammatory cytokines, 39 and susceptibility is associated with increased Th2 and decreased Th1 cytokine production. 13,[15][16] Therefore, our SNPs could code for HLA allele variation, which in turn could affect antigen-binding capacity and CD4 ϩ cell polarization, thereby contributing to a protective or risk immunophenotype.…”
Section: Discussionmentioning
confidence: 99%